Identifikasi Bakteri dan Efektivitas Antibiotik dalam Pengencer untuk Mengontrol Pertumbuhan Bakteri pada Semen Sapi Friesian Holstein - Rabusin, Muttaqinullah; Andriani, Andriani; Arifiantini, Raden Iis; Karja, Ni Wayan Kurniani (Jurnal Veteriner; Vol 20 No 1 (2019), 2019)
This study was designed to investigate the presence of bacterial species in Friesian Holstein (FH) bovine semen at the time of collection, processing and to assess the efficacy of two types of antibiotics combinations; penicillin and streptomycin (PS) and gentamycin, tylosin, lincomycin and spectinomycin (GTLS) in semen extender on bacterial control and quality of semen.  For this purpose, three experiments were conducted.  In experiment 1, identification of bacterial content in fresh semen which collected from 5 bovine ejaculates.  In experiment 2, identification of bacterial content in skimmilk-eggyolk extender which were prepared in artificial insemination center, Lembang, Bandung. In experiment 3, identification of bacterial content in frozen thawed semen.  In the result, some of bacterial species were isolated from the bovine semen.  The GTLS combination of antibiotics may be incorporated into a freezing extender or protocol without compromising the post-thawed semen quality of FH bull spermatozoa.  Three types of bacteria were found in fresh semen; Klebsiella sp., Micrococcus sp., and Pediococcus sp..  Three types of bacteria were found in semen extender; Enterobacter cloacae, Pseudomonas diminuta and Serratia plymutica.  Two types of bacteria were found in frozen semen; Enterobacter cloacae and Serratia plymutica.  In conclusion, antibiotics PS and GTLS were effective for controlling the growth of bacteria in frozen semen.